Morphophysiological aspects of the digestive tract in IV stage larvae of Bradysia impatiens (Diptera: Sciaridae) - Marín-Cruz, Victor Hugo; Rodríguez-Navarro, Silvia; Barranco-Florido, Juan Esteban; Terrón-Sierra, Roberto Alejandro; Cibrián-Tovar, David (Revista Colombiana de Entomología, 2019)
The morphological, cytological and physiological aspects of the digestive tract of the siarid Bradysia impatiens fourth-instar larvae were studied using bright-field microscopy. The division of the digestive tract into the stomodeum (foregut), the mesenteron (midgut) and the proctodeum (hindgut) was observed; the second of which being composed of endocrine, regenerative, column-shaped cells. The larvae did not present a crop; hence digestion of the bolus occurs in the midgut. They have two well-developed gastric caeca, where it can be assumed that great nutrient absorption takes place. The peritrophic membrane is type II, with a pore size that allows the passage of molecules up to 150 kDa, and which divides the midgut into two regions: the endoperitrophic and ectoperitrophic spaces. There are four Malpighian tubules present. The midgut has a pH gradient ranging from mildly alkaline in the foregut to neutral in the caeca and hindgut. It has a recirculation mechanism stretching from the endoperitrophic to the ectoperitrophic space and vice versa, which improves digestion and optimizes enzyme production. The morphophysiological features observed in B. impatiens larvae confirm that these organisms are well-adapted detritivores. Additionally, the peritrophic membrane protects the midgut from pathogenic agents.